2017
DOI: 10.18844/ijlt.v9i1.2225
|View full text |Cite
|
Sign up to set email alerts
|

Models in science and for teaching science: Data from an intervention programme

Abstract: Abstract     Currently, implementing models and modelling activities in science teaching is considered to be essential. Apart from being crucial as an auxiliary aid to the construction of scientific knowledge, they also play a major contribution in the development of adequate views of nature of science and models, as well as in the development of scientific inquiry competencies. However, many studies disclose that science teachers do not rely on models in their classes very often, thus reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
4
6
0
Order By: Relevance
“…Several PSTs stated that they had drawn a macroscopic picture of what they had seen. This finding is in line with multiple studies showing that PSTs hold naïve and simplistic views of models as replicas or copies of a real system prior to model-or modelling-based interventions (Danusso et al, 2010;Soulios & Psillos, 2016;Torres & Vasconcelos, 2017;Yenilmez Turkoglu & Oztekin, 2016). All science teachers should understand the meaning of a model beyond it merely being a copy or replica (Oh & Oh, 2011).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Several PSTs stated that they had drawn a macroscopic picture of what they had seen. This finding is in line with multiple studies showing that PSTs hold naïve and simplistic views of models as replicas or copies of a real system prior to model-or modelling-based interventions (Danusso et al, 2010;Soulios & Psillos, 2016;Torres & Vasconcelos, 2017;Yenilmez Turkoglu & Oztekin, 2016). All science teachers should understand the meaning of a model beyond it merely being a copy or replica (Oh & Oh, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…A Danish study showed that in-service teachers thought it was important to teach meta-knowledge about models to pupils but that more experienced teachers tended to be more focused on modelling processes in their teaching than less experienced ones (Nielsen & Nielsen, 2019). After participating in modelling interventions, PSTs also saw a greater need for meta-modelling knowledge for their pupils, such as the limitations of models and their use in science (Torres & Vasconcelos, 2017). These results suggest the importance of including scientific modelling in science teacher education for PSTs with or without previous degrees in science (Danusso et al, 2010) as well as for in-service teachers (Nielsen & Nielsen, 2019).…”
Section: (2) 2021mentioning
confidence: 99%
See 3 more Smart Citations